Observation of Z‐DNA Structure via the Synthesis of Oligonucleotide DNA Containing 8‐Trifluoromethyl‐2‐Deoxyguanosine. Issue 1 (20th January 2021) - Bao, Hong‐Liang; Xu, Yan
Abstract: This article contains detailed synthetic protocols for the preparation of DNA oligonucleotides containing 8‐trifluoromethyl‐2′‐deoxyguanosine ( CF3 dG) and their application to observe Z‐DNA structure in vitro and in living HeLa cells. First, using a catalytic system consisting of FeSO4, H2 SO4, and H2 O2 in DMSO, we achieved a one‐step synthesis of CF3 dG through a radical reaction between deoxyguanosine (dG) and CF3 I, with a yield of 45%. We then obtained the 3′‐phosphoramidite of CF3 dG through a routine three‐step procedure. Next, we employed the CF3 dG phosphoramidite monomer in the synthesis of oligonucleotides on a solid‐phase DNA synthesizer. Finally, we used the CF3 dG‐modified DNA oligonucleotides to observe Z‐DNA structure in vitro and in living HeLa cells through 19 F NMR spectroscopy. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of CF3 dG phosphoramidites Basic Protocol 2 : Preparation of CF3 dG‐modified DNA oligonucleotides Basic Protocol 3 : Evaluation of CF3 dG stabilization of Z‐DNA structure by CD spectroscopy Basic Protocol 4 : Investigation of Z‐DNA structure in vitro and in HeLa cells with CF3 dG‐modified DNA oligonucleotides and 19 F NMR spectroscopy